Chibe be Idollized - Louie Belledo, Lourdes Cahilig, Rowel Costales, Rita Maree Delos Santos, Abigael gallano, Noel Moreno, Jyre Dominic Obligacion, Marielyn Padilla, Dina Poldo, Samantha Samson and Laiza Abigail Prinsipe. 4 0 16; 5
u
Business Plan: (BSBA major in Management) - Pamantasan ng Lungsod ng Maynila, 2008.
Keywords: 2 -- 0; 6; 20; 20; 2